PP53 New Medical Device Law: Germany's Experience With Refund Restrictions - Müller, Elvira; Neeser, Kurt; Oelze, Ilse-Barbara (International journal of technology assessment in health care, 2018)
Introduction:Since 2005, new hospital examination and treatment methods (NUB) were reimbursed by hospital individual supplementary fees as long as they were not sufficiently covered by a DRG. In 2016, the NUB procedure was decisively changed by legal norm §137 h SGB.V to evaluate medical devices (MD) of high risk classes, particularly invasive, or new theoretical-scientific concepts versus treatment alternatives by the Federal Joint Committee (G-BA). Hospitals and manufacturers have to submit detailed information on the application of the MD and the scientific evidence to G-BA along with a NUB application. This assessment may lead to exclusion of the method from reimbursement by the statutory health insurance (SHI).Methods:The published MD consultation submissions, assessments and G-BA resolutions (to date) were analyzed regarding evaluation criteria, treatment potential and study obligation.Results:In 2017, nineteen procedures were reviewed by G-BA with respect to §137 h. Two ultra-controlled high-intensity focused ultrasound (HIFU) indications were regarded as having potential benefit but not sufficient evidence yet, thus respective studies have to be initiated. Three procedures were regarded as eligible according to §137 h but not yet evaluated. Six procedures (ultra-controlled HIFU in five indications, targeted lung denervation in chronic obstructive pulmonary disease) were rated as having no potential benefit, while eight procedures were regarded as not eligible according to §137 h.Conclusions:Initially put into place for high risk class and primarily invasive devices, consultations and assessments under §137 h show that there is some uncertainty around applicability criteria. The majority of those procedures which fell under the assessment law failed to be granted potential benefit as treatment alternative. Currently consultations are ongoing which could possibly lead to the exclusion of these methods from the performance spectrum of the SHI. Manufacturers should revise their study concepts in order to fulfill the specific demand for robust evidence.